Use of Stirred Suspension Bioreactors for Male Germ Cell Enrichment - Sakib, Sadman (Methods Mol Biol, 2016)
Spermatogenesis is a stem cell based system. Both therapeutic and biomedical research applications of spermatogonial stem cells require a large number of cells. However, there are only few germ line stem cells in the testis, contained in the fraction of undifferentiated spermatogonia. The lack of specific markers makes it difficult to isolate these cells. The long term maintenance and proliferation of nonrodent germ cells in culture has so far been met with limited success, partially due to the lack of highly enriched starting populations. Differential plating, which depends on the differential adhesion properties of testicular somatic and germ cells to tissue culture dishes, has been the method of choice for germ cell enrichment, especially for nonrodent germ cells. However, for large animals, this process becomes labor intensive and increases variability due to the need for extensive handling. Here, we describe the use of stirred suspension bioreactors, as a novel system for enriching undifferentiated germ cells from 1-week-old pigs. This method capitalizes on the adherent properties of somatic cells within a controlled environment, thus promoting the enrichment of progenitor cells with minimal handling and variability.